2011
DOI: 10.3354/dao02367
|View full text |Cite
|
Sign up to set email alerts
|

Viral encephalopathy and retinopathy outbreak in freshwater fish farmed in Italy

Abstract: Viral encephalopathy and retinopathy (VER), otherwise known as viral nervous necrosis (VNN), is a neuropathological condition affecting > 40 species of fish. Although VER affects mainly marine fish, the disease has also been detected in certain species reared in freshwater environments. There are relatively few reports concerning the disease in freshwater species, and there is not much information on clinical signs. Nevertheless, the most common clinical findings reported from affected freshwater species are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 28 publications
3
38
1
3
Order By: Relevance
“…To date, the disease has been reported in more than 50 fish species, mainly marine with the greatest impact being in striped jack, European sea bass (Dicentrarchus labrax), groupers, and flatfishes [4,5]. A few outbreaks have also been documented in freshwater farms [6,7]. Recently, the disease has been considered as the most serious viral threat affecting marine farmed species in the Mediterranean region, thus representing one of the bottlenecks for further development of the aquaculture industry [8].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the disease has been reported in more than 50 fish species, mainly marine with the greatest impact being in striped jack, European sea bass (Dicentrarchus labrax), groupers, and flatfishes [4,5]. A few outbreaks have also been documented in freshwater farms [6,7]. Recently, the disease has been considered as the most serious viral threat affecting marine farmed species in the Mediterranean region, thus representing one of the bottlenecks for further development of the aquaculture industry [8].…”
Section: Introductionmentioning
confidence: 99%
“…Betanodavirus isolated from Epinephelus taurine (taurine Epinephelus Nervous Necrosis Virus=ETNNV) has high homolouges with virus isolated from freshwater fish Poecili areticula (Guppy Nervous Necrosisvirus=GNNV) [20]. Virus isolated fromMicropterus salmoides has high homologous with RGNNV [22]. In this study, VNN infected tilapia has homologous with RGNNV.…”
Section: Rt-pcr and Sequencingmentioning
confidence: 85%
“…Infected fish demonstrate erratic swimming patterns and the neurological abnormalities, including cellular necrosis andvacuolization in the retina and the system of central nervous [19]. Some studies suggest that the VNN was not only attack the sea waterfish species,but also attack the freshwater fish species like an ornamental fish, guppy, Poicelia reticulata [20], Acipenser sp [21], fish medaka (Oryzias latipes) [19], largemouth black bass Micropterus salmoides [22], and tilapia, Oreochromis niloticus (L.) [23] [24].The genetic characterization confirmed that VNN infecting freshwater fish species was belong to the RGNNV genotype [19][25] [24] and the SJNNV genotype [19].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical signs of fish with NNV infections are uncoordinated or erratic swimming behavior and loss of appetite (Kuo et al, 2011). More than 40 species of fish from all continents, with the exception of Africa, that belong to the orders Anguilliformes, Perciformes, Pleuronectiformes, Tetraodontiformes, and Gadiformes are susceptible to NNV (Bovo et al, 2011). Epizootic NNV in marine aquaculture has been reported in several Asian countries, particularly China and Japan, and often leads to rapid mortality generally during early fry and fingerling stages (Furusawa et al, 2006;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%